2013
DOI: 10.1371/journal.pone.0054264
|View full text |Cite
|
Sign up to set email alerts
|

Screening of a Specific Peptide Binding to VPAC1 Receptor from a Phage Display Peptide Library

Abstract: Background/PurposeThe VPAC1 receptor, a member of the vasoactive intestinal peptide receptors (VIPRs), is overexpressed in the most frequently occurring malignant tumors and plays a major role in the progression and angiogenesis of a number of malignancies. Recently, phage display has become widely used for many applications, including ligand generation for targeted imaging, drug delivery and therapy. In this work, we developed a panning procedure using a phage display peptide library to select a peptide that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Binding phages were eluted and their titers calculated in each round, and the gradual increase in enrichment indicated that the phages bound strongly to nsp7. Immobilized nsp7 was a fusion protein with 6× His tags, and purified His-tag protein was therefore used to exclude false positive phages, as described previously (Tang et al, 2013). DNA sequencing identified five consistent 12-amino-acid peptide sequences in the final three rounds.…”
Section: Discussionmentioning
confidence: 99%
“…Binding phages were eluted and their titers calculated in each round, and the gradual increase in enrichment indicated that the phages bound strongly to nsp7. Immobilized nsp7 was a fusion protein with 6× His tags, and purified His-tag protein was therefore used to exclude false positive phages, as described previously (Tang et al, 2013). DNA sequencing identified five consistent 12-amino-acid peptide sequences in the final three rounds.…”
Section: Discussionmentioning
confidence: 99%
“…8 Thus, it is urgent toÂŻnd an innovative Fig. 9 But, the clinic usage of the antibodies against these target molecules is limited because of their strong heterogeneity to human body. method for the early detection and eÂźective therapy of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, our research group identified a novel dodecapeptide that could specifically bind to the VPAC1 receptor with high affinity using a phage display peptide library. The results imply that the peptide may serve as a potential molecular imaging probe and therapeutic agent (87). Increasing the therapeutic window, which can be achieved by reducing the radiation toxicity to normal organs, could significantly enhance the therapeutic effects through increased injected radioactivity.…”
Section: Prospective and Conclusionmentioning
confidence: 97%